Rancang Bangun Penjejak Matahari Untuk Optimasi Daya Panel Surya - Marhatang Marhatang; Yiyin Klistafani; Fitra Firdaus; Ahmad Yani (Politeknik Negeri Ujung Pandang, 2023)
The limitation in energy provision has become quite a crucial issue. The oil reserves in Indonesia continue to decline, and a similar situation is occurring with coal reserves. Thus, a conventional and renewable energy source is needed that does not harm the environment, for example, solar energy. This research aims to harness solar energy that can still be converted into electrical energy, and it also aims to improve the power output of solar panels for better optimization. The research starts by planning the motor, battery capacity, and solar panel capacity. Field testing is conducted at Merdeka Field, Ujung Pandang State Polytechnic, and data is collected under two conditions: with the use of a sun tracker and without a sun tracker. The power output obtained from each solar panel is then calculated. Based on the research results, the testing using a sun tracker yielded a power output of 17,857 Watts with a horizontal position of 47° Northeast and a vertical position of 15° at 11:30 AM WITA (Central Indonesia Time). Meanwhile, during the testing without a sun tracker, it resulted in a power output of 16.2 Watts with a horizontal position of 0° North and a vertical position of 5° at 1:00 PM WITA, indicating an average increase of 43.03%.